An Analysis of Factors that Predict Hospital Readmission after Surgery for Perforated Appendicitis. Issue 9 (September 2017) - Millien, Jeffanne E.; Townsend, Michael; Goldberg, Joshua; Fuhrman, George M.
We performed this study to develop an understanding of why patients were readmitted after appendectomy for perforated appendicitis. Patients who required surgery for perforated appendicitis during a recent five-year period were identified. We recorded the demographic data, length of symptoms, length of stay, vital signs, laboratory findings, surgical approach, length of surgery, time to readmission, length of readmission, and intervention required after readmission. We divided the cohort into two groups depending on whether the patient was readmitted. We used chisquared analysis and t test to determine differences between the two groups. We identified 86 patients, with 14 (16.3%) requiring readmission. The only factors that predicted readmission were longer appendectomy surgery (P = 0.03) and open surgery (P = 0.04). After readmission, one patient required reoperation, and two required percutaneous abscess drainage. The remaining 11 patients were readmitted for a median of two days, received intravenous fluids, and required no additional clinically significant management. Patients requiring longer and open surgery are at an increased risk for hospital readmission after resection of a perforated appendix. Efforts to reduce readmission will likely be most successful if hydration and brief periods of clinical observation can be arranged when necessary for patients after discharge from surgery.